Greenhouse gas balance associated with sugarcane production in South-Central Brazil, considering the management and expansion - Bordonal, Ricardo de Oliveira (2016)
The substitution of fossil fuel with sugarcane ethanol aiming to reduce emissions of greenhouse gases (GHGs) has recently been debated because of the possible emissions incurred from land use change (LUC). This work was based on GHG inventory from cultivation and LUC of recently established sugarcane plantation in south-central Brazil, with the purpose of estimating the impact of expansion on GHG balance, including emissions and removals due to LUC. Changes in quantity and quality of soil carbon (C) upon conversion of diverse agricultural systems (coffee, citrus, annual crops and pasture) to sugarcane in southern Brazil were also assessed through field experiments. The estimates show that sugarcane cultivation and its expansion during 2006-2011 in south-central Brazil presented an overall accumulated GHG balance of 217.1 Tg CO2eq by 2030, including emissions from cultivation activities and emissions/removals due to LUC. Expansion of sugarcane plantation contributed to attenuate part of GHG emissions from agricultural production phase. Similarly, the ethanol C offset by displacing fossil fuels could readily payback that C deficit. The data obtained by field experiments show that the LUC of coffee and citrus to sugarcane depleted soil C stock by 21.5% (26.8 Mg C ha-1) and 23.6% (34.9 Mg C ha-1) in the 0-100 cm layer after a period of 3 and 4 years, respectively. In contrast, there was no significant difference in soil C stocks in 0-100 cm depth upon conversion of pasture and annual crop into sugarcane. However, only the conversion of pasture into sugarcane decreased soil C stock in 0-20 cm depth, with depletion of 13.3 Mg C ha-1 (43.9%) over 8 years after the LUC. With regard to the quality of soil C, the data of Laser-Induced Fluorescence Spectroscopy (LIFS) showed that the higher the losses of soil C, the greater was the humification index (HLIFS) of soil organic matter (SOM). In general, conversion of the agrosystems (e.g., coffee, citrus, annual crop and pasture) into sugarcane increased HLIFS of SOM. For some depths, HLIFS more than doubled in comparison with the previous land uses. We expect that the results achieved in this work may contribute to the development of actions and public policies to strengthen strategies for GHG mitigation and ensure the environmental benefits of sugarcane ethanol in Brazil.